Економіко-математичне моделювання кадрово-інтелектуальної захищеності підприємства - Головень, О.В.; Клопов, І.О. (Культура народов Причерноморья, 2013)
Стаття присвячена вирішенню актуальної проблеми підвищення ефективності управління кадрово-інтелектуальною захищеністю підприємства. Запропоновано комплекс взаємозв'язаних моделей визначення рівня кадрової безпеки промислового підприємства Статья посвящена решению актуальной проблемы повышения эффективности управления кадрово-интеллектуальной защищенностью предприятия. Предложен комплекс взаимосвязанных моделей определения уровня кадровой безопасности промышленного предприятия. The article is devoted to the decision of the issue of the day of increase of management efficiency skilled-intellectual safety enterprises. Was offered the complex of associate models of determination of skilled strength of industrial enterprise security. Personnel security, as part of the company economic security, aims to work with such personnel, the establishment of labor and ethical relationships that could have been defined as "no loss". All this activity is not a single area in Functional HR manager, but only fits well into it. To evaluate the personnel and intellectual protection offered to distribute the employees in the following characteristics: knowledge and competencies, because all it involves the concept of competence, intelligence, character traits that directly affect the efficiency of labor. As to the degree of motivation, then there is a problem in using this option because it has situational, that is due to the external environment. Development of motivation and incentives is one of the tasks of service management. Personnel and intellectual component of the enterprise security into account the level of education, training, performance management and professional production staff. The main objective in evaluating personnel and protection of intellectual enterprise is qualitatively assess such intangible concepts as knowledge and competencies personnel.